The impact of the USD/EUR exchange rate on Bulgaria’s foreign trade - Lyubomir Lyubenov (Икономика и компютърни науки, 2022)
The USD/EUR rate, with its volatility, is one of the most significant factors and measure of processes in the global economy. Specifically, its influence is most significant on each country's foreign trade. The article aims to make only this impact on the import and export of Bulgaria – before and after our country's entry into the EU, which also pre-defies the period considered. Based on the theory of elasticity and the use of single-factor linear regression models, for the first time the elasticity of imports and exports, in general and energy resources, is assessed against the USD/EUR exchange rate. Limitations to the study turned out to be multi-collinearity in modelling and different economic conditions before and after entering the EU. The negative effects of the exchange rate prevail on imports. It is found that in the future there is a possibility of greater energy dependence of Bulgaria, predetermined by the significant influence of the USD/EUR exchange rate. The conclusions drawn suggest that there may be a delay effect (lag) in the time of its impact. This allows experimentation with models of distributed lags, but only with data after Bulgaria's entry into the EU. From a research point of view, it is also of interest to study the impact of the USD/EUR exchange rate on specific groups of goods of exports and imports.